Different presentations in patients with tumor necrosis factor receptor-associated periodic syndrome mutations: report of two cases - Çelebi-Tayfur, Aslı; Bilginer, Yelda; Finetti, Martina; Gattorno, Marco; Özen, Seza (The Turkish Journal of Pediatrics, 2013)
Tumor necrosis factor receptor-associated periodic syndrome (TRAPS) is an autosomal dominant autoinflammatory disorder caused by mutations in the TNFRSF1A gene encoding the 55-kDa receptor for tumor necrosis factor (TNF)-α. It is characterized by recurrent prolonged episodes of fever accompanied by abdominal pain, pleuritis, migratory skin rashes, fasciitis, headache, conjunctivitis, and periorbital edema. We report two children, one with a severe mutation in the TNFRSF1A gene causing the typical phenotype. The second patient had a homozygous R92Q-type mutation and displayed a periodic fever with aphthous stomatitis, pharyngitis and adenitis (PFAPA) syndrome-like phenotype. In the eastern Mediterranean region, TRAPS is probably underdiagnosed because of the overwhelming frequency of familial Mediterranean fever (FMF). However, TRAPS should be sought for in patients with atypical symptoms for FMF.